Modifying JPS algorithm using NavMesh Data Structure applied in 3D using unity - Hannah Shane Gittabao, Raymond Carlos Medina. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology), Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2